Haunch Beams Behavior And Performance In High-Rise Buildings With Spectrum And Pushover Response - Gali Pribadi; Rinda Karlinasari (Universitas Islam Sultan Agung, 2026)
Indonesia is located in an active tectonic zone with high seismic potential, so that high-rise building structures are very vulnerable to earthquake loads. One alternative to improve structural performance is the use of haunch beams, a non-prismatic beam model with varying stiffness in length. This study examines the effectiveness of haunch beams in improving the seismic performance of the SRPMK system, a 60 m high building without shear walls and with varying column dimensions along the building height. Prismatic beams (50/35) and haunch beams (100/35) with varying lengths of 1/5L, 1/4L, and 1/3L were used in the beam-column connection. The analysis was carried out using the response spectrum method and the nonlinear static pushover method. The results of the pushover analysis study, with the 1/3L haunch beam configuration, provided better structural performance in controlling drift and displacement, especially in high-rise buildings with columns that taper upwards. The nonlinear static procedure method (pushover) showed that the 1/3L haunch beam variant showed the most effective performance. Pushover X, displacement 0.384 m, base shear 18813.17 kN, drift 1.24% ≤ 2%, category IO-LS range, pushover Y, displacement 0.271 m, base shear 18343.3 kN, drift 0.83% ≤ 1%, limit category IO. Smaller drift values indicate increased stiffness of the frame system. B-Haunch 1/3 L provides better structural performance in controlling drift and displacement, especially in tall buildings with columns that taper upwards. Smaller drift values indicate increased stiffness of the frame system. The addition of shear walls later will increase stiffness, making the building structure safer in resisting lateral loads.